Dynamics of Islamic Education in Kalimantan: Uncovering the Strategy of Dissemination and Assimilation in the Early Days - Nur, Zulfikah; Rama, Bahaking; Syamsuddin, Syamsuddin (Green Publisher Indonesia, 2024)
It is known that the periodization of the entry of Islam into Indonesia is classified as one of the four major immigration that forms the socio-cultural ecosystem of the Indonesian people, including the spread of Islam in South Kalimantan during that period. After the four major immigration periods, only then did the European colonial nations enter which started from the Portuguese, Spanish, Dutch and finally Japanese. This study uses a qualitative method with a library research approach. Islam entered Kalimantan in the 15th century A.D.A.D. by peaceful means brought by missionaries from Java. Sunan Bonang and Sunan Giri have students in Kalimantan, Sulawesi, and Maluku. Sunan Giri's composition is called Kalam Muyang, while Sunan Bonang's composition is called Sumur Serumbung. Islamic education in Kalimantan in the course of history has its own pride, with the publication of a person who received the title